(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Numerous initiatives have been undertaken to safeguard cultural heritage, including reconstruction and restoration efforts led by various stakeholders. One such case is the traditional village of Wae Rebo, where the Mbaru Niang houses serve as a prominent example of preservation through the faithful reconstruction of architectural form and structural integrity. Since Wae Rebo developed into a tourist destination in 1997, Mbaru Niang has experienced multiple reconstruction phases, each time maintaining its original shape—a form intrinsically linked to both its function and symbolic meaning. This interconnectedness is particularly evident in vernacular architecture, where function, form, and meaning are inherently interrelated. These observations prompt critical questions: Do current preservation practices uphold the original relationship among function, form, and meaning? And to what extent does preserving the same form influence their functional and symbolic roles? This research aims to examine the architectural dimensions of function, form, and meaning of Mbaru Niang in Wae Rebo Village by employing qualitative methods, including field observations and interviews. The study aspires to enrich the discourse surrounding Wae Rebo’s architectural heritage while offering a critical perspective on traditional structures subjected to conservation practices.